Vitamin D3 capsulation using maillard reaction complex of sodium caseinate and tragacanth gum - Fatemeh Navab; Atefe Rezaei; Mohammad Hossein Rouhani; Farnaz Shahdadian; Mahsa Alikord (Food Chemistry: X)
The encapsulation of vitamin D3 (VitD3) using the Maillard reaction complex of sodium caseinate-tragacanth gum (TG) to the production of water-soluble vitamins were studied. Spray drying was used to prepare the complex. Its physicochemical properties, stability, and release characteristics were evaluated. The results showed that containing sodium caseinate- Tragacanth gum (TG) 1 % (w/v) and VitD3 1 % (w/v) had the highest encapsulation efficiency (71 %). The resulting microcapsules showed suitable particle size, strong negative zeta potential, and good stability with spherical morphology. Thermal and spectroscopic analyses showed proper interaction between wall and core components. In vitro, release and simulated digestion studies demonstrated the ability of microcapsules to protect VitD3 under gastric conditions and provide controlled release in the intestine. This encapsulation system shows potential for enriching food with VitD3 and increasing its stability and bioavailability.